DEMOKRASI SEBAGAI BENTUK KOMUNIKASI POLITIK KAUM REMAJA - Nabus, Ephivani Kuartis; Chontina Siahaan (Program Studi Akuntansi IKOPIN, 2021)
Political communication is an aspect that is always found in the worldpolitical.Political communication is very important, especially indemocracy.Democracy is a form of political communication to convey thesovereignty of the people. This journal was created with the aim thateveryone can know about democracy in adolescents and how important therole of youth or youth in the world of democracy.This journal also has benefitsfor both the author himself and his readers.In this manufacture, the authoruses the literature method and collects data about the material and analyzesand draws coclusions. You are a teenager or democracy id an individual whoplays an important role in democracy to achieve common prosperity.Withoutthe youngers generation all general election or regional election which areforms of democracy will not be able to take place in general,fair,honest,andfree. Young people are entered into voting rights when they start at the age of17 or who are married,they have the same civic responsibilities as otheradults. There are many things that youth touch in democracy,such as physicalworks and photos that show how many important democracy is for teenagers.